1996
DOI: 10.1302/0301-620x.78b3.0780369
|View full text |Cite
|
Sign up to set email alerts
|

Foreign-Body Reaction and the Course of Osteolysis After Polyglycolide Implants for Fracture Fixation

Abstract: Foreign-body reaction to polyglycolide (PGA) implants has been described in man. Many animal experiments have verified the mechanical properties of fixation devices made from PGA, but a significant foreign-body reaction has not been described. We studied the effect of PGA rods in 12 sheep with standardized osteochondral fractures of the medial femoral condyle fixed with uncoloured, self-reinforced PGA rods (Biofix). Radiographs were taken at intervals ranging from two weeks to two years, and the sheep were kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(78 citation statements)
references
References 54 publications
1
66
1
7
Order By: Relevance
“…Foreign-body reactions can be provoked with implant volumes that exceed the capacity of the surrounding soft tissues [32]. Recent recommendations suggest using the minimum possible implant size to reduce the amount of breakdown products [33].…”
Section: Discussionmentioning
confidence: 99%
“…Foreign-body reactions can be provoked with implant volumes that exceed the capacity of the surrounding soft tissues [32]. Recent recommendations suggest using the minimum possible implant size to reduce the amount of breakdown products [33].…”
Section: Discussionmentioning
confidence: 99%
“…Acute synovitis of the knee has been described in three patients after fixation of osteochondral fragments with PGA pins, 5,6 but there was no long-term follow-up. The association between osteolytic changes and foreign-body tissue responses to PGA has been well documented in experimental 20,21 and clinical studies, 8,10,11,22 but the natural history of such lesions is not clear. We have confirmed in our study that there is usually total regression of the osteolysis within three years.…”
Section: Discussionmentioning
confidence: 99%
“…[96][97][98] Studies have furthermore shown that osteolysis and sterile fi stulae are common symptoms within 0.5 to 4 years after implantation. [93][94][95][99][100][101][102] Additionally, polymers, especially PLLA, cause a signifi cant swelling of soft tissue in a post-surgery period from 2.5 to 6 years. [ 96 ] Studies also identify encapsulated debris as a result of the polymeric degradation process.…”
Section: Reviewmentioning
confidence: 99%